Current Situation and Utilization of Velvet Deer Germplasm Resources in China - Lixin Tang; Xiaobin Wen; Ranran Zhang; Xiumei Xing (Animals, 2022)
Velvet deer are not only a representative special economic animal but also an important part of livestock. With the increasing awareness of international competition for germplasm resources in China, more and more attention has been paid to the protection and utilization of germplasm resources. However, there is poor understanding about velvet deer resources. Therefore, we are providing a comprehensive introduction of Chinese velvet deer germplasm resources from the aspects of ecological distribution, domestication and breeding.